Interpretation of the Quran in contemporary India: Wahiduddin Khan’s reading of peace and spirituality in the scripture - Okawa, Reiko (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the interpretation of the Quran (tafsir) of an Indian Muslim intellectual, Wahiduddin Khan (b.1925), written as a commentary on his translation of the Quran, The Quran: English Translation, Commentary and Parallel Arabic Text. It aims to illustrate how Khan created a peaceful understanding of the Quran in contemporary India, where a critical need to resolve the issue of violent communalism between Muslims and Hindus existed. Two main subjects are argued here: (1) the background to Khan’s thought and (2) the features of his interpretation of the Quran. Khan was deeply influenced by the Islamic and Indian trends of thought in contemporary India, such as Islamism (Tablighi Jamaʻat), Islamic revivalism (Jamaʻat-e Islami) and non-violence (Gandhism), and chose his own peaceful and spiritual understanding of Islam. This background is reflected in his interpretation of the Quran, implying that the recognition of scripture provides an awareness of the inner self which leads the way to live peacefully with non-Muslims. We discuss that this interpretation of the Quran is meaningful to build a pluralistic peaceful environment inside and outside India, since it tries to avoid actual conflict between Muslim and non-Muslim while keeping the priority of the Islamic faith.